Application of a Technology-Based Data Collection System for the Writing Class of the IAIN Cirebon Student Da'wah Institute - Yolanda Silpia Irani; Salsabiela Azzahra (Pusat Teknologi Informasi dan Pangkalan Data IAIN Syekh Nurjati Cirebon, 2023)
Effective data management plays a crucial role in optimizing the performance of educational institutions. This study aims to explore the implementation of a technology-based data management system for writing classes in the Student Preaching Institution of the State Islamic Institute (IAIN) Cirebon. The objective is to improve the efficiency and effectiveness of data collection, storage, and analysis, ultimately enhancing the overall quality of the writing classes. This research utilizes a mixed-methods approach, incorporating qualitative and quantitative data collection techniques. Firstly, a comprehensive review of the existing data management practices is conducted to identify the limitations and challenges faced by the institution. Secondly, a technology-based data management system is developed, integrating modern tools and techniques to streamline the data collection process. The system is designed to facilitate easy data entry, retrieval, and analysis, ensuring accurate and reliable information for decision-making purposes. The implementation of the technology-based data management system is evaluated through a series of case studies and interviews with relevant stakeholders. The findings reveal several significant benefits, including increased efficiency in data management, improved accuracy in reporting, and enhanced collaboration among the stakeholders involved in the writing classes. Moreover, the system enables the institution to track the progress of individual students, identify their strengths and weaknesses, and provide targeted interventions to support their learning and development. The results of this study contribute to the growing body of literature on the application of technology in educational institutions. The findings highlight the importance of leveraging technology to optimize data management processes, particularly in the context of writing classes in the Student Preaching Institution of IAIN Cirebon. The insights gained from this research can serve as a valuable resource for other educational institutions seeking to enhance their data management practices and improve the overall quality of their programs.